P-177 Non-invasive aneuploidy testing versus conventional morphological embryo selection in good prognosis patients. (30th June 2022) - Franco, J; Carrillo de albornoz, E; Amelia, V; Gonzalo, B; Florencia, S; Ivan, O; Alvaro, M; Silvia, I; Elena, M; Alejandra, R; Beatriz, B; Ana, V; et al.
Abstract: Study question: Can non-invasive preimplantation genetic testing of aneuploidies (niPGT-A) improve the clinical outcome in good prognosis patients compared to morphological embryo selection without aneuploidy testing? Summary answer: Embryonic cell-free DNA (cfDNA) in the blastocyst culture medium offers more objective information for blastocyst selection, resulting in higher ongoing pregnancy rate in good-prognosis patients. What is known already: One of the biggest challenges in IVF is accurately selecting viable embryos that are most likely to produce a healthy child at home after embryo transfer. Trophectoderm biopsy and PGT-A have improved implantation and clinical pregnancy rates per transfer; however, two recent studies have shown that PGTA does not improve clinical pregnancy rates below 35 years. A non-invasive alternative is to analyze (the cfDNA) in blastocyst culture medium. Several studies have shown that cfDNA testing on blastocyst culture medium at day 6 of development allows detection of aneuploidies with high concordance rates compared to TE biopsy and inner cell mass Study design, size, duration: This observational study reports data from September 2020 to December 2021. During this period, niPGT-A was performed on 25 patients under 35 years of age whit average age of 32, where cfDNA analysis was applied to the culture medium of 92 blastocysts. A total of 20 single embryo transfers (SETs) have been performed so far, comparing the results with 31 transfers performed in the same period based only on morphological criteria. Participants/materials, setting, methods: In the niPGT-A group, embryos were cultured in a Geri incubator up to day-4, and then individually cultured in 10 µl drops of CCSS (Fujifilm) until day 6 in an ESCO –system whit low oxygen concentration. At day-6, blastocysts were vitrified, and media collected in sterile PCR tubes after at least 40 hours in culture. After collection, media were immediately frozen and analyzed by Next Generation Sequencing analysis. Deferred transfer was performed according to media results. Main results and the role of chance: In the niPGT-A group euploidy rate was 57% whit 8% non- informative results. Pregnancy rate was 80% with 75% ongoing pregnancy and 5% miscarriage rates, having 8 live births up to now. For the morphology group, pregnancy rate was 58% with 55% ongoing pregnancy and 3% miscarriage rates. We did a secondary analysis identifiying which blastocyst we would be transfered, if only morphology would be considered. We observed that in 65% of the cases we would choose the same embryo as with niPGT-A, however in 35% of the cases we would have transferred a blastocyst with an aneuploid medium. Regarding blastocyst quality for throphoectoderm classified as A, B or C the euploidy rate were 62%, 58% and 33% respectively, and pregnancy rates were 100%, 78% and 33%. For inne cell mass, similar euploidy rates werw observed for blastocyst classified as A, B or C (59%, 52% and 57% respectively) and pregnancy rates were 100%, 73% and 100%. Evaluating the expansion grade in blastocoel no differences were observed in euploidy rates for cathegories 4, 5 and 6 (52%, 54% and 50% respectively) and pregnancy rates were 82%, 100% and 100%. We observed the lower pregnancy rate for blastocysts whit throphoectoderm C previously suggested by other authors. Limitations, reasons for caution: Our results are encouraging since this group of good prognosis could improve their ongoing pregnancy rate even having a good reproductive prognosis whit morphology selection. Larger randomized controlled trials are needed to verify and extend our findings in this age range Wider implications of the findings: These results support the clinical application of niPGT-A in the laboratory routine as a proritization tool, without the need of embryo manipulation, reducing subjectivity for blastocyst selection compared to morphology and increasing the ongoing pregnancy rate in good prognosis patients Trial registration number: Sa-16552/19-EC:428